2022
DOI: 10.3390/biology11030356
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Taxonomic Approach Points towards a Single-Species Hypothesis for Santolina (Asteraceae) in Corsica and Sardinia

Abstract: Santolina is a plant genus of dwarf aromatic shrubs that includes about 26 species native to the western Mediterranean Basin. In Corsica and Sardinia, two of the main islands of the Mediterranean, Santolina corsica (tetraploid) and S. insularis (hexaploid) are reported. Along with the cultivated pentaploid S. chamaecyparissus, these species form a group of taxa that is hard to distinguish only by morphology. Molecular (using ITS, trnH-psbA, trnL-trnF, trnQ-rps16, rps15-ycf1, psbM-trnD, and trnS-trnG), cypsela … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…In this scenario, it has been demonstrated that homoploid hybrid speciation [ 21 ] can play a crucial role in the emergence of new species [ 23 , 24 ], given that all species tested so far are diploid, with 2 n = 2 x = 18 chromosomes [ 16 , 25 , 26 ]. The use of nrDNA and (maternally inherited) cpDNA markers helps to elucidate the phylogenetic relationships even under hybridization scenarios [ 27 , 28 ]. Armeria arenaria (Pers.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, it has been demonstrated that homoploid hybrid speciation [ 21 ] can play a crucial role in the emergence of new species [ 23 , 24 ], given that all species tested so far are diploid, with 2 n = 2 x = 18 chromosomes [ 16 , 25 , 26 ]. The use of nrDNA and (maternally inherited) cpDNA markers helps to elucidate the phylogenetic relationships even under hybridization scenarios [ 27 , 28 ]. Armeria arenaria (Pers.)…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, there is need to use an integrated approach to address the taxonomy [9] of these putative subspecies. To achieve a sound taxonomic circumscription, we performed morphometric analyses, including living populations from type localities, complemented by seed morpho-colorimetry, karyotype asymmetry estimation, molecular systematics, and comparative niche analysis (for similar integrative approaches, see [27,28]). In this study we aim: (1) to test the current taxonomic circumscription; (2) to verify the occurrence in Italy of A. arenaria subsp.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on image analysis and its aim is to detect differences in the external size and shape of diaspores of different populations/groups of populations. It was successfully used in several studies to detect differences among taxonomically critical species groups, providing data useful for taxa delimitation (Sarigu et al, 2019; De Giorgi et al, 2022; Tiburtini et al, 2022). A set of 100 cypselae for each population was acquired with a flatbed scanner (Epson Perfection V550) with a digital resolution of 1200 dpi.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the current taxonomic delimitation of Santolina species from southern France and north‐eastern Spain is based exclusively on qualitative morphological observations (Tison & de Foucault, 2014; Tison et al, 2014). The aim of the present study is to test the current three‐species taxonomic hypothesis, using an integrated approach already successfully applied in Santolina (De Giorgi et al, 2022), involving morphometric analysis of adult plants and cypselae, niche similarity, and phylogenetic analysis (plastid markers trnH‐psbA , trnL‐trnF , trnQ‐rps16 , rps15‐ycf1 , psbM‐trnD , and trnS‐trnG ).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, on one side, there is the need to build sound taxonomic hypotheses using multiple lines of evidence (see, e.g., [ 15 , 16 , 17 , 18 ]); on the other hand, given the ongoing mass extinctions and the decline of taxonomists in academies [ 19 , 20 ], there is the need to speed up the recognition and description of biodiversity on earth. In this respect, citizen science could also be helpful [ 21 ], for instance in observing and capturing plant diversity with a coverage and frequency much higher than by just relying on academic scholars.…”
mentioning
confidence: 99%